Финитная абсолютная непрерывность гауссовских мер на бесконечномерных пространствах - Рябов, Г.В. (Український математичний журнал, 2008)
Вивчається поняття фінітної абсолютної неперервності для мір на нескінченновимірних просторах. Для гауссівських продакт-мір на R∞ та гауссівських мір на гільбертовому просторі отримано критерії фінітної абсолютної неперервності. Розглянуто випадки, коли умова фінітної абсолютної неперервності гауссівських мір рівносильна умові їх еквівалентності. A notion of finite absolute continuity for measures on infinite-dimensional spaces is studied. For Gaussian product-measures on R∞ and Gaussian measures on a Hilbert space, criteria for the finite absolute continuity are obtained. Some cases are considered, where the condition of the finite absolute continuity of the Gaussian measures means the equivalence of these measures.